2014
DOI: 10.1186/1556-276x-9-447
|View full text |Cite
|
Sign up to set email alerts
|

Potentiating antilymphoma efficacy of chemotherapy using a liposome for integration of CD20 targeting, ultra-violet irradiation polymerizing, and controlled drug delivery

Abstract: Unlike most malignancies, chemotherapy but not surgery plays the most important role in treating non-Hodgkin lymphoma (NHL). Currently, liposomes have been widely used to encapsulate chemotherapeutic drugs in treating solid tumors. However, higher in vivo stability owns a much more important position for excellent antitumor efficacy in treating hematological malignancies. In this study, we finely fabricated a rituximab Fab fragment-decorated liposome based on 1,2-bis(10,12-tricosadiynoyl)-sn-glycero-3-phosphoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 37 publications
1
34
0
Order By: Relevance
“…Rituximab (Rtx), the first US FDA (Food and Drug Administration)-approved monoclonal antibody (mAb) for treating non-Hodgkin lymphoma (NHL), targets the CD20 antigen and leads to CD20 + B-cell depletion [1][2][3][4]. Currently, Rituximab is routinely incorporated into all phases of conventional treatment, including first-line therapy, maintenance and salvage therapy [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Rituximab (Rtx), the first US FDA (Food and Drug Administration)-approved monoclonal antibody (mAb) for treating non-Hodgkin lymphoma (NHL), targets the CD20 antigen and leads to CD20 + B-cell depletion [1][2][3][4]. Currently, Rituximab is routinely incorporated into all phases of conventional treatment, including first-line therapy, maintenance and salvage therapy [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Although clinical applications have proven unprecedented success of Rituximab in treating a variety range of non-Hodgkin lymphomas (NHLs), only 48% of patients respond to the treatment, with a complete remission (CR) rate of less than 10% [2]. Moreover, tumor relapse is inevitable for most patients [3,4]. Previous studies demonstrated that the exhaustion and anergy of effector cells and complements are involved in the limitations of Rituximab based immunotherapy [5,6].…”
Section: Introductionmentioning
confidence: 96%
“…2 However, this pharmacokinetic sweet spot can hardly be achieved due to the distinctly different transient states of drugs in adhesion, distribution, metabolism and excretion (ADME). [3][4][5] Moreover, cancer cells tend to develop drug resistance, especially multidrug resistance (MDR), during the prolonged course of chemotherapy, characterized by cancer progression or recurrence. [3][4][5] Moreover, cancer cells tend to develop drug resistance, especially multidrug resistance (MDR), during the prolonged course of chemotherapy, characterized by cancer progression or recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…3,7 With the development of material science and nanotechnology, nanoparticles based drug delivery systems (DDS) offer new hopes for improving the efficiency of chemotherapy with the following potential advantages: rstly, nanoparticles with desired size (e.g., 100-200 nm in diameter) could escape from the reticuloendothelial system (RES) to realize a favorable in vivo stability in the circulating blood. 2,5,11 Finally, nanoparticles are not physically recognized as substrates by the ATP-binding cassette (ABC) efflux pumps, which are proved to be overexpressed on chemo-resistant cancer cells and can extrude toxins from cells, conferring MDR to a broad spectrum of cytotoxic agents. 9,10 Thirdly, nanoparticles decorated with various ligands, such as monoclonal antibodies (mAbs), can realize targeted delivery and thus enhance internalization of encapsulated agents into tumor cells via endocytosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation